2009
DOI: 10.1007/s10661-009-0978-6
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations in surface sediments from two regions (Saros and Gökova Gulfs) of the Eastern Aegean Sea

Abstract: The main goal of this study is to determine the present heavy metal pollution state in the two gulfs of the Aegean Sea; Saros and Gökova Gulfs. The surface sediments were collected from 11 and eight locations in the Saros and Gökova during May 2001, respectively. The results showed that the sediments of Saros and Gökova gulfs were polluted with Pb, Cr, Zn, Mn, and Ni and Pb, Cr, Ni, and Mn, respectively. For various metals the contamination factor (CF) has been calculated to assess the degree of pollution in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…The oceanography of the Gökova Bay has not been studied until now. However, several studies on water masses and water quality can be found for İzmir Bay (Sayın, 2003;Sayın et al, 2006Sayın et al, , 2007 and Saros Bay (Tokat, 2006;Tokat and Sayın, 2007;Pazı, 2008;Sayın and Beşiktepe, 2010;Uluturhan, 2010).…”
mentioning
confidence: 99%
“…The oceanography of the Gökova Bay has not been studied until now. However, several studies on water masses and water quality can be found for İzmir Bay (Sayın, 2003;Sayın et al, 2006Sayın et al, , 2007 and Saros Bay (Tokat, 2006;Tokat and Sayın, 2007;Pazı, 2008;Sayın and Beşiktepe, 2010;Uluturhan, 2010).…”
mentioning
confidence: 99%
“…Marine sediments provide useful information for environmental and geochemical research about marine pollution (Uluturhan, 2009). Therefore, sediments are ecologically important components of the marine environment and have been contaminated by inorganic and organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, there are so many studies on sedimentology and geochemistry of sediments in the Aegean Sea (Küçüksezgin, 2001;Dalman et al, 2006;Pekey, 2006;Uluturhan, 2009;Esen et al, 2010). Each of the scientist have been assessed one or two accumulation indexes and have been commented about that indexes results.…”
Section: Introductionmentioning
confidence: 99%
“…Metals are a class of important anthropogenic inorganic pollutants and due to their various health-related problems and widespread environmental occurrences, they have garnered much attention around the world (Paulson et al 2006;Yalcin, Narin, and Soylak 2007;Lalah, Ochieng, and Wandiga 2008;Liu et al 2009;Hiller, Jurkovic, and Utriepka 2010;Uluturhan 2010). Certain trace elements, Cr, Cu, Ni, and Zn, are essential micronutrients required for the normal growth and function of organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Certain trace elements, Cr, Cu, Ni, and Zn, are essential micronutrients required for the normal growth and function of organisms. Other trace elements like Cd, Hg, and Pb are considered toxic with respect to human health and aquatic life (Uluturhan 2010). In aquatic ecosystems, sediments are the main sink for these metals but when environmental conditions change (pH, redox potential, particle size, etc.…”
Section: Introductionmentioning
confidence: 99%